PENGARUH AKTIVITAS UPACARA KEAGAMAAN UMAT HINDU TERHADAP PEREKONOMIAN PEDAGANG DI PASAR BADUNG - Aprilia, Ni Ketut; Andayani, Ni Made; Ayustini, Ni Luh (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2019)
Bali is the name of one of the provinces in Indonesia. Bali is located between Java and Lombok. The capital is Denpasar, which is located in the southern part of the island. In the world, Bali is famous as a tourism destination with a unique variety of arts and culture, especially for Japanese and Australian tourists. Bali is also known as the Island of the Gods and Pulau Seribu Island. Bali which is famous for its art and culture has various places and tourism potentials that pamper every tourist visiting Bali. The majority of the population of Bali are Hindus. Many Balinese who are Hindus have activities related to their religious ceremonies based on their celebrations or so-called